"Bold and Ragged": A Cross-Cultural Case for the Aesthetics of Melodic Angularity. (24th September 2020) - Carter-Ényì, Aaron; Carter-Ényì, Quintina
Smaller corpora and individual pieces are compared to a large corpus of 2, 447 hymns using two measures of melodic angularity: mean interval size and pivot frequency. European art music and West African melodies may exhibit extreme angularity. We argue in the latter that angularity is motivated by linguistic features of tone-level languages. We also found the mean interval sizes of African-American Spirituals and Southern Harmony exceed contemporary hymnody of the 19th century, with levels similar to Nigerian traditional music (Yorùbá oríkì and story songs from eastern Nigeria). This is consistent with the account of W. E. B. Du Bois, who argued that African melody was a primary source for the development of American music. The development of the American spiritual coincides with increasing interval size in 19th-century American hymnody at large, surpassing the same measure applied to earlier European hymns. Based on these findings, we recommend techniques of melodic construction taught by music theorists, especially preference rules for step-wise motion and gap-fill after leaps, be tempered with counterexamples that reflect broader musical aesthetics. This may be achieved by introducing popular music, African and African Diaspora music, and other non-Western music that may or may not be consistent with voice leading principles. There are also many examples from the European canon that are highly angular, like Händel's "Hallelujah" and Schönberg's Pierrot Lunaire . Although the tendency of textbooks is to reinforce melodic and part-writing prescriptions with conducive examples from the literature, new perspectives will better equip performers and educators for current music practice.